IMPLIKASI YURIDIS UNDANG-UNDANG TANPA TANDA TANGAN PRESIDEN DALAM MEWUJUDKAN GOOD GOVERNANCE - Surya Efendi; Edi Haskar; Nessa Fajriyanafarda (Ensiklopedia of Journal, 2023)
According to Article 20 Paragraph (5) of the 1945 Constitution of the Republic of Indonesia, further explained in Article 73 Paragraph (4) of Law Number 13 of 2022 concerning the second Amendment to Law Number 12 of 2011 concerning Formation of Legislation, if the DPR and the President have approved the draft law, but the President does not approve it, then 30 days after approval of the draft, it will automatically officially and legally become law. This study aims to examine the juridical implications of the law without the president's signature in achieving good governance, as well as analyze the reasons for not signing the law. The method used in this study is a normative juridical method, in which the data obtained comes from library research. This approach involves collecting data through official documents, books, and research results related to the topic being researched. Based on the results of the research, it was found that the juridical implications of laws without the president's signature on efforts to realize good governance are creating opportunities for the public to participate in the governance of the laws produced, in order to prevent laws that are formally and juridically flawed, by submitting a judicial review to the Constitutional Court. The underlying reason for the President's non-signature of the law is the potential for controversy and unrest in society.